Data Science in Engineering, Volume 9 Proceedings of the 40th IMAC, A Conference and Exposition on Structural Dynamics 2022 - Madarshahian, Ramin; Hemez, Francois (Conference Proceedings of the Society for Experimental Mechanics Series, 2022)
VIII, 156 p. 124 illus., 109 illus. in color.